Prioritizing Restorative Justice in the Settlement of the Sumbang Besak Adultery Case in Babeko Village, Jambi - Fitri Habi, Nuraida; Adawiyah, Robi'atul; Harun, Hermanto; Kurniawan, Ardian; Roni, Rusli Abdul (El-Mashlahah, 2024)
This research examined resolving customary violations of sumbang besak in Babeko Village, Jambi, by prioritizing restorative values in customary law. Research in the context of this social realm tried to look at customary law as a whole, whether it is still regressive or is influenced by the significance of restorative discourse, which has been progressive. The aim of this research was not only to find out the mechanism for resolving conflicts and imposing punishment but also to look at the role and concept of traditional law in Babeko Village restoring disturbed relationships. Using empirical research methods and an anthropological juridical approach, data was collected through interviews with traditional leaders, observations of traditional communities, and documentation and review of related literature. The findings of this research find out the strength of the Babeko Village customary legal system, which has successfully implemented a restorative approach by prioritizing the recovery of victims, violators, and affected communities. Prioritizing dialogue and reconciliation is important in resolving cases, to produce fair and sustainable results. This concept can then become a reference in the development of the national legal system, specifically in alternative dispute resolution models.